MicroRNA-17-5p promotes chemotherapeutic drug resistance and tumour metastasis of colorectal cancer by repressing PTEN expression - Fang, Lekun; Li, Haoran; Wang, Lei; Hu, Jun; Jin, Tianru; Wang, Jianping; Yang, Burton B (Oncotarget, 2014)
Colorectal cancer (CRC) is one of the most common cancers worldwide, especially in Western countries. Although chemotherapy is used as an adjuvant or as a palliative treatment, drug resistance poses a great challenge. This study intended to identify biomarkers as predictive factors for chemotherapy. By microarray analysis, we studied miRNAs expression profiles in CRC patient, comparing chemoresistant and chemosensitive groups. The miRNAs of interest were validated and the impact on clinical outcomes was assessed in a cohort of 295 patients. To search for potential targets of these miRNAs, tissue samples were subject to in situ hybridization and immunohistochemistry analysis. Colorectal adenocarcinoma cells were also used for in vitro experimentation, where cellular invasiveness and drug resistance were examined in miRNA-transfected cells. The expression level of miRNA-17-5p was found increased in chemoresistant patients. Significantly higher expression levels of miR-17-5p were found in CRC patients with distant metastases and higher clinical stages. Kaplan-Meier analysis showed that CRC patients with higher levels of miR-17-5p had reduced survival, especially in patients who had previously received chemotherapy. Overexpression of miR-17-5p promoted COLO205 cell invasiveness. We found that PTEN was a target of miR-17-5p in the colon cancer cells, and their context-specific interactions were responsible for multiple drug-resistance. Chemotherapy was found to increase the expression levels of miR-17-5p, which further repressed PTEN levels, contributing to the development of chemo-resistance. MiR-17-5p is a predictive factor for chemotherapy response and a prognostic factor for overall survival in CRC, which is due to its regulation of PTEN expression.